University Webometrics Ranking Analysis using SWOT and Gap Analysis - Batubara, Abdul Karim; Purwaningtyas, Franindya; Putri, Raissa Amanda (Khizanah al-Hikmah : Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan, 2023)
The Webometrics ranking serves as a crucial metric for assessing the quality and online visibility of universities. In this investigation, the study employs a SWOT analysis approach to delineate the strengths, weaknesses, opportunities, and threats influencing university Webometrics rankings. The primary objective is to scrutinize Webometrics rankings through the dual lenses of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) and Gap analysis. The approach includes collecting Webometrics ranking data from reliable sources, followed by an in-depth SWOT analysis to identify the factors that impact the university’s position in the Webometrics ranking. Additionally, gap analysis is applied to assess disparities between the current Webometrics ranking and the university’s aspirations. Through gap analysis, the study identified areas where the university has the potential to enhance its Webometrics standing. The study’s findings are anticipated to offer valuable guidance for universities seeking to elevate their Webometrics rankings.